Errors And Problems Faced by The Students in Practicing Consecutive Interpreting - Mohd Tahir, Asman; Murni Sekar Pinilih (EDUJ : English Education Journal, 2023)
This research aims to analyze the errors and problems faced by the students in practicing English to Indonesian consecutive interpreting. This study is conducted in an interpreting class of six semester English Letters students of IAIN Surakarta. This study was conducted to know the students’ types of errors and problems in practicing consecutive interpreting. This is a descriptive-qualitative research. It presents the data with a content analysis method. This research uses documentation, error validation, and interviews to answer the research questions. The data were gained by collecting the students’ performance videos in practicing consecutive interpreting and establishing interviews to get additional information. The results showed that among 159 errors, which were occurred during the students’ performances, the errors can be classified into 8 types. They are errors in non-conservation of paralinguistic features, omission, distortion, inadequate language proficiency, literal translation, addition, register conservation, protocol, procedure and ethics. The non-conservation paralinguistic features are the most frequent error with 57 occurrences (35.8%) and the least common error found is protocol, procedure and ethics with 2 occurrences (1.3%). Those errors were caused by the students’ problems. The results show that there are 8 types of problems faced by the students, including nervosity, English proficiency, lack of practice, interpretation partner, classmates, time pressure, confidence and public speaking skills. Overall, the students need more practice and knowledge, especially in English proficiency and need guidance in solving their problems to improve their interpretation skills.